Modern problems and hypotheses of general theory of law: Succession and novation - Aklim Khatypovich Khaziev, Ravya Faritovna Stepanenko, Nataliia Olegovna Khazieva,; Rybakov, Oleg Yuryevich (Opción, 2019)
The article is devoted to the consideration of the general theory of law issues in modern conditions of the Russian statehood development via system analysis of the phenomenon of law as a method. As a result, Ideal law, being the sphere of pure duty, turned on itself as the highest normative-value. In conclusion, the process of evolution of states continues its historically centuries-old procession, retaining continuity and developing the field of research activity innovations in socio-humanitarian science, including law.